An Observational Study of Teacher’s Gestures in EFL Classroom - Aulia Urrohimah; Ista Maharsi (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2022)
Verbal utterances and nonverbal utterances are acknowledged to be semantically and pragmatically coexpressive. Previous theories reveal that gestures are useful for teacher’s conceptual planning of messages and student’s comprehension and learning motivation. This study is carried out using an observational study and aimed to give insight into the use of gestures by EFL teacher during the teaching in the language classroom. An Islamic senior high school EFL teacher with a bilingual classroom become the participant of this study. A video recording is put on the back of the classroom aimed to capture the teacher’s gestures and the teacher and the students’ interaction, an audio recording is placed on the teacher’s front table, and the researcher is on the corner of the classroom to observe the teaching process synchronously. The data collected were transcribed then analysed using AS-Unit for recognizing the English utterances and the categorization of gestures was adopted from Wang and Loewen (2016). The finding elaboratively describes the use of gestures (i.e., iconics, metaphorics, deictics, beats, head movements, affect displays, kinetographs, and emblems) produced by the teacher in her classroom utterances. The finding shows that the gestures take a big part in supporting the teacher as speaker in teacher’s complex lexical retrieval. Also, the visual of the use gestures is provided. Therefore, the result of this study serves as a teaching reflection and can be employed as a model to provide language learning comprehensible input in the language classroom.